Economic performance of sports clubs charitable status in Poland - Artur Wyszyński (Nicolaus Copernicus University in Toruń, 2015)
The main aim of this article is to assess the financial condition and results of Polish football clubs who have the status of public benefit organizations (OPP). The analysis was conducted for clubs that were played matches in the 2013/2014 season in the men's football tournament at all levels except the highest such competitions. Ekstraklasa (no clubs having the status OPP) for levels I, II, III, IV league and class district, A , B and C. All the clubs analyzed as a function of the association. The analysis shows that clubs are in a bad financial situation. Most clubs, regardless of the grade level in which the matches were played were characterized by a low value of wealth. Average debt was close to 100%. As a result, nearly one-third of the clubs showed a negative equity value. About half of the clubs observed a negative value total return on assets and return on sales. In the structure of revenues are the primary source of public funds. Other sources of income included clubs, private funds, other and income from the 1% tax on individuals